Uma abordagem baseada em medição interna para avaliar eficiência energética de aplicativos Android - Fischer, Leonardo Matthis (2015)
The increase of application complexity on mobile devices like smartphones and tablets demands more computational resources consuming more energy. The concern with consumption is aggravated by slow and limited development of batteries. To reduce energy consumption is necessary to identify system bottlenecks and for that, tools are required to evaluate energy consumption. Most of the available tools employ hardware models to estimate energy consumption, whether in a physical device or simulator. For providing accurate results, models at high level of detail and specific to a hardware platform are required. On the other hand, measurement techniques, although more accurate have used external instrumentation, which are not accessible and not practical for developers and end users. Therefore, flexible tools should be developed, which should be independent of a specific hardware and useful for developers and end-users. This work proposes a new approach to estimate consumption, which is based on power measurement techniques using samples of voltage and current extracted from the battery of the device driver itself. This approach is able to measure the energy consumption of an Android application, or parts of its code. Results achieved by this method show that it maintains a consistency of measured values in relation to other approaches.